KEKUATAN ALAT BUKTI KETERANGAN SAKSI YANG MEMILIKI HUBUNGAN DARAH DENGAN TERDAKWA DALAM PROSES PEMBUKTIAN DI PENGADILAN - SARI, APRI MONA; ', Erdianto; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Proofing process in the trial is passed by a process of examination of evidence of witness testimony. In this case, the researcher wants to know the verification process of Decision Number 106 / Pid.B / 2013 / PN.Pbr, then Decision Number 272 / Pid.Sus / 2017 / PN.Pbr, and Decision Number 451 / Pid.Sus / 2017 / PN.Pbr, because in some of these verdicts the witness is someone who has a blood relationship with the defendant. However, in Decision Number 46 / Pid.Sus / 2013 / PN.SLW witness who has a blood relationship with the defendant can not be presented as a witness in court due to having a blood relationship with the defendant. The type of this research is normative juridical that is to analyze the provisions rather than the legislation seen from the decisions by the judge, using secondary data obtained from primary law material, secondary law material and tertiary legal material. Data collection techniques for legal research is used literature review method and data analysis used deductive analysis, which is drawing the conclusions of the general arguments to the arguments of a special nature.It can be concluded based on the formulation of the problem of the first researcher, the evidentiary process of witness testimony that has blood relation with the defendant is not all criminal acts are allowed for witnesses who have blood relation giving testimony in the hearing, the setting of witnesses is also unclear and has no legal certainty. Secondly, the basis of the judge's consideration in deciding on the evidence of witness testimony that has a blood relation with the defendant in this proofing process is that of the decision number 106 / Pid.B / 2013 / PN.PBR, 272 / Pid.Sus / 2017 /PN.PBR, and verdict number: 451 / Pid.Sus / 2017 / PN.PBR provides consideration for witnesses who have a blood relationship, and in the decision number: 46 / Pid.Sus / 2013 / PN.SLW for witnesses who have a relationship blood can not be filed as a witness in court for violating Article 168 of the Criminal Procedure Code, in which the witness having blood relation is presented as a lightening witness to the defendant. The first author's suggestion should be to authorized officials to make the law more thorough in its manufacture. More systematic preparation, let alone related to the problem of the witness should be arranged more fully and clearly. Second, crimes committed within the family should be resolved in a familial way, if it is still possible to settle with the family itself rather than finally through legal proceedings in court.Keywords: Proof Process Description of Witness Having Blood Relation with Defendant - Legal Certainty.